Simulation of characteristics of gamma-radiation detectors based on mercury compounds - Skrypnyk, A.I.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Prokhorenko, E.M.; Klepikov, V.F.; Lytvynenko, V.V. (Вопросы атомной науки и техники, 2013)
We used Monte-Carlo method to compare characteristics of HgI₂- and HgS-detectors which work in the mode of pulse amplitude analysis. The GEANT4 Simulation Toolkit version 4.9.4p04 and EGSnrc version 4.r2.3.2 were used for modeling gamma-quantum trajectories and calculating response functions in the gamma-quantum energy range between 25 keV and 3 MeV.We supposed that simulated HgI₂- and HgS-detectors were equipped with planar contacts and their geometric sizes were 3.14 mm² × 1 mm. Basing on calculated detector's response functions, we obtained the efficiency of gamma-quantum registration and detector sensitivity dependence on energy for energy range from 0.025 to 3 MeV. Statistical characteristics of theoretical response functions and amplitude distributions of pulses are studied taking into account noise and incomplete charge collection distortions of theoretical response functions. Results of simulation show that in the high-energy region the efficiency of energy conversion of gamma-quanta in charge signal for HgS detectors can exceed the same characteristic for HgI₂-detectors up to 10. . . 12 percents. Метод Монте-Карло використаний для порiвняння характеристик HgI₂-i HgS-детекторiв, якi працюють у режимi аналiзу амплiтуд iмпульсiв. Для моделювання траекторiй гамма-квантiв та розрахунку функцiй вiдгуку детекторiв в областi енергiй вiд 25 кеВ до 3 МеВ використанi пакети GEANT4 v4.9.4p04 i EGSnrc v4.r2.3.2. Дослiджуванi детектори були оснащенi планарними омiчними контактами, а їх розмiри були 3,14 мм² × 1мм. У дiапазонi енергiй 0,025...3 МеВ для детекторiв були розрахованi ефективнiсть реєстрацiї гамма-квантiв i залежнiсть чутливостi вiд енергiї. Показано, що в областi порiвняно високих енергiй гамма-квантiв ефективнiсть перетворення енергiї квантiв у зарядовий сигнал для HgS-детекторiв може перевищувати ефективнiсть HgI₂-детекторiв на 10...12 вiдсоткiв. Метод Монте-Карло использован для сравнения характеристик HgI₂-и HgS-детекторов, которые работают в режиме анализа амплитуд импульсов. Для моделирования траекторий гамма-квантов и расчета функций отклика детекторов в области энергий от 25 кэВ до 3 МэВ использованы пакеты GEANT4 v4.9.4p04 и EGSnrc v4.r2.3.2. Исследуемые детекторы были оснащены планарными омическими контактами, а их размеры были 3,14мм² × 1мм. В диапазоне энергий 0,025...3 МэВ для детекторов были рассчитаны эффективность регистрации гамма-квантов и зависимость чувствительности от энергии. Показано, что в области сравнительно высоких энергий гамма-квантов эффективность преобразования энергии квантов в зарядовый сигнал для HgS-детекторов может превышать эффективность HgI₂-детекторов на 10...12 процентов.